2014
DOI: 10.1063/1.4894716
|View full text |Cite
|
Sign up to set email alerts
|

Compact electro-absorption modulator integrated with vertical-cavity surface-emitting laser for highly efficient millimeter-wave modulation

Abstract: We demonstrate a compact electro-absorption slow-light modulator laterally-integrated with an 850 nm vertical-cavity surface-emitting laser (VCSEL), which enables highly efficient millimeter-wave modulation. We found a strong leaky travelling wave in the lateral direction between the two cavities via widening the waveguide width with a taper shape. The small signal response of the fabricated device shows a large enhancement of over 55 dB in the modulation amplitude at frequencies beyond 35 GHz; thanks to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This VCSEL amalgamates laterally with a compact transverse cavity, targeting an augmented modulation efficiency within the millimeter-wave spectrum for high-speed modulations in datacenter networks. The empirical findings on this coupled cavity VCSEL are congruent with the theoretical modeling result, indicating a 60% increase in the small-signal modulation bandwidth [25]. To increase the transmission distance in fiber, the modal dispersion in multi-mode fiber (MMF) could be reduced using single mode VCSELs.…”
Section: Introductionsupporting
confidence: 77%
“…This VCSEL amalgamates laterally with a compact transverse cavity, targeting an augmented modulation efficiency within the millimeter-wave spectrum for high-speed modulations in datacenter networks. The empirical findings on this coupled cavity VCSEL are congruent with the theoretical modeling result, indicating a 60% increase in the small-signal modulation bandwidth [25]. To increase the transmission distance in fiber, the modal dispersion in multi-mode fiber (MMF) could be reduced using single mode VCSELs.…”
Section: Introductionsupporting
confidence: 77%
“…Therefore, this resonance is referred to as “photon-photon resonance” [13]. Similar effect is observed in vertical-cavity surface-emitting lasers (VCSELs) coupled to a transverse cavity [22], in which the photon-photon resonance is induced by transverse oscillating modes. Because the shown IM responses have an unused frequency between the frequency f 3 dB and the enhanced mm-narrow bands, this modulation enhancement is not favored for applications in telecommunications.…”
Section: Resultsmentioning
confidence: 89%
“…Most recently the author's group [20] has newly reported using strong OFB to boost the modulation frequencies over an ultrahigh frequency passband over 55 GHz and has shown improvement of the gain of a corresponding RoF link by about 20 dB. Such enhancement in the IM response over an ultrahigh frequency passband was attributed as a type of photon-photon resonance due to coupling of oscillating modes in the coupled cavity [13, 21, 22]. It is obtained when the nonmodulated laser keeps operation in CW under strong OFB.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the authors demonstrated resonance modulation centered on a frequency of 40 GHz with large enhancement of over 30 dB in the modulation amplitude . This resonance modulation was proved to be due to photon–photon resonance (PPR) between two transverse oscillating modes under strong slow‐light feedback . This PPR results in an additional resonance peak to the modulation response at frequencies that potentially exceed the conventional carrier‐photon resonance (CPR) frequency a few times .…”
Section: Introductionmentioning
confidence: 95%